DIGITAL TRANSITION, CBDC READINESS, AND BANK FUNDING STABILITY IN UZBEKISTAN (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This paper examines whether the recent digital transition of commercial banks in Uzbekistan has been associated with changes in liquidity-related funding indicators. The analysis is motivated by policy discussions on central bank digital currency (CBDC) and by the broader concern that a more digital financial environment may alter the stability of bank deposits and the structure of bank funding. Because a fully implemented retail CBDC is not yet directly observable on bank balance sheets in the sample period, the study uses bank-level digital intensity as a proxy for CBDC readiness and exposure to digital transition. The empirical analysis is based on a balanced panel of 26 commercial banks for 2021–2026. The dataset combines assets, capital, loans, deposits, the structure of loans and deposits by client type, and digital infrastructure indicators such as bank cards, payment terminals, ATMs, infokiosks, and terminal turnover. A difference-in-differences design with bank and year fixed effects is used to compare more digital banks with less digital banks after 2023. The main dependent variable is the loan-to-deposit ratio, while the deposit-to-asset ratio and retail deposit share are used as robustness checks. The estimated interaction effect is positive for the loan-to-deposit ratio and the deposit-to-asset ratio, but statistically insignificant once bank-clustered standard errors are applied. Overall, the results do not support the view that stronger digitalization necessarily weakens bank funding stability. Instead, the findings suggest that banks with stronger digital infrastructure were able to maintain broadly stable funding patterns during the recent stage of digital financial transformation.
Keywords: CBDC; bank liquidity; digital finance; deposits; commercial banks; Uzbekistan; difference-in-differences.